Risk assessment and modeling for underground cavern project construction - Chua, Aden Ming Jian. (2010)
This Final Year Project (FYP) Report covers the basic knowledge of risk assessment for an underground rock cavern construction project as well as developing a risk model for a case study. Even though there are several risks involved in a construction project, the main concern in this FYP report will be the economic risk factors such as the construction cost and time. Hence, these two factors will be of highest priority in choosing the type of risk analysis method to be used to perform the risk assessment. The different types of risk involved will be discussed followed by a brief introduction to the risk assessment methodology.